Mauritania - Senegal: An emerging New African gas province:is it still possible? - Mostefa A. Ouki (The Oxford Institute for Energy Studies, 2020)
Over the last five years, Africa's MSGBC geological basin situated in five African countries: Mauritania, Senegal, Gambia, Guinea Bissau, and Guinea Conakry has started to attract increased interest from international oil and gas companies (IOCs). The Grand Tortue Ahmeyim (GTA) gas field development project, overlapping Mauritania and Senegal's offshore waters, is a key example. This project is a unique case of cooperation and partnership between two African countries and IOCs (BP and Kosmos Energy) in a potentially new African natural gas province. The focus of the GTA gas development project is a floating liquefied natural gas (FLNG) export project. This would make available natural gas supplies not only for exports, but also for the domestic energy markets of Mauritania and Senegal. Due to the Covid-19 pandemic, the commissioning of the first phase of the GTA project, which was initially planned for 2022, has been delayed to 2023. The capacity of this Phase 1 FLNG project is about 2.5 mtpa . The subsequent phases of this LNG export project, if and when approved, are expected to potentially expand the project's LNG export capacity to 10 mtpa. Furthermore, two other separate LNG projects with a 10 mtpa LNG capacity each are planned or under consideration in Mauritania and Senegal. This is a huge LNG export capacity for these two countries. Can these on-going and planned gas developments transform Mauritania and Senegal into a new emerging African gas province.
Keywords: 330; LNG; Mauritania; Natural gas; NG 163; NG163; North Africa; Senegal; West Africa